Alkaloids from endophytic fungus Aspergillus fumigatus HQD24 isolated from the Chinese mangrove plant Rhizophora mucronata. Issue 19 (21st September 2022) - Zou, Renjian; Wei, Chengwen; Zhang, Xuexia; Zhou, Dongdong; Xu, Jing
Abstract: Chemical investigation of endophytic fungus Aspergillus fumigatus HQD24, isolated from the flower of Rhizophora mucronata led to the isolation of eight alkaloids, including pyripyropene A (1 ), 1, 11-dideacetyl-pyripyropene A (2 ), pyripyropene E (3 ), chaetominine (4 ), tryptoquivaline J (5 ), fumitremorgin C (6 ), 1-acetyl-β-carboline (7 ), and nicotinic acid (8 ). Their structures were unambiguously elucidated on the basis of extensive spectroscopic data and comparison with the data of literature. Compound 2 was known as a synthetic product and isolated as a natural product for the first time. The immunosuppressive and cytotoxic activities of all isolated compounds were evaluated. Graphical Abstract: UF0001